The Letter XV. The Devil's Arcana.: Dialogues between the archetypes of carnival and tarot. (The Voz a Vos Bulletin, 2024)
The play Mystical Triptych. Polaroid, snapshots of a night, is the result of a project that evaluates the research-creation model proposed by the researcher, from the point of view of complexity. This evaluation takes place in a creative experience that starts from thinking about the construction of love and heartbreak in 6 actress-researchers who live between the 20th and 21st centuries.In this construction of the imagination about love, we arrive at the tarot, and through it, the fifteenth arcanum, The Devil. However, by collecting the data from the mental and mystical levels of the researchers, the devil, as a character, atmosphere, and essence of the work, is constructed as the festive devil of the carnival.This paper shows the trajectories of knowledge production that the researchers-creators have in the creation of the play.